Raccontare la Resistenza a scuola Esperienze e riflessioni - Bravi, Luca; Martinelli, Chiara; Oliviero, Stefano (Public History of Education. Teorie, esperienze, strumenti, 2022)
The book aims at collecting papers discussed during the online webinars Raccontare la Resistenza a scuola organised between April 2021 and May 2021. The book aims at consolidating links between theoretical and historical reflection and didactical practises: it deals with the domain of history of applied education and Public History of Education. Hence, the book has been defined for been used by university students and teachers as a reliable and viable tool. The volume answers to ancient requests made by the scholastic world. Furthermore, it gives a contribute to the historical-educative debate concerning a still empty dominion.